Regulation of white adipogenesis and its relation to ectopic fat accumulation and cardiovascular risk. Issue 1 (July 2015) - Gustafson, Birgit; Smith, Ulf
Abstract The subcutaneous adipose tissue (SAT) is the largest and least harmful adipose depot to store excess lipids. However, SAT has a limited ability to expand and recruit new cells. When the SAT adipose cells become expanded (hypertrophic obesity), this leads to a dysregulated and dysfunctional SAT and the accumulation of ectopic fat in many depots. Increased hepatic and visceral fat are well-known ectopic fat depots and reflect the inability of SAT to accommodate excess fat. Ectopic fat also leads to paracrine and endocrine effects and promotes the metabolic profile of the Metabolic Syndrome. In addition, ectopic fat accumulation in and around the heart and vessels are considered to be active and cross talk with the tissues, thereby enhancing several aspects associated with the risk of developing cardiovascular disease and atherosclerosis.